2014
DOI: 10.1177/1535370214561587
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the WWOX in pathogenesis and endocrine therapy of breast cancer

Abstract: Breast cancer is one of the most common malignancies, often with complicated etiology and poor clinical outcome. In recent years, a critical role has emerged for the WW domain-containing oxidoreductase (WWOX) in breast cancer. WWOX is a tumor suppressor; it is deleted or attenuated in 29-63.2% of breast cancer tissues and is associated with a poor prognosis of breast cancer patients. WWOX heterozygous knockout mice show a higher incidence of mammary tumors and impaired branching morphogenesis. At the molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…4 ). Altogether, an incomplete list of the proteins that apparently mediate ERBB4 function via physical and functional interactions with the ERBB4 cytoplasmic domain includes the Rous sarcoma virus protein tyrosine kinase (SRC); the Abelson-related protein tyrosine kinase (ABL2); the spleen-associated protein tyrosine kinase (SYK); the Janus kinase 1 (JAK1); protein tyrosine phosphatase non-receptor type 11 (PTPN11); phospholipase C gamma-2 (PLCG2); phosphatidylinositol 4,5-bisphosphate 3-kinase catalytic subunit alpha isoform (PIK3CA) via its p85 regulatory subunit; the Casitas B-lineage lymphoma ubiquitin ligase (CBL); the second guanine nucleotide exchange factor named after the sixth letter of the Greek alphabet (VAV2); the rat sarcoma virus protein (RAS) GTPase activating protein RASA1; the signal transducer and activator transcription factors STAT1 and STAT5a; the Yes-associated protein 1 (YAP1); the tumor suppressor oxidoreductase WWOX; postsynpatic density protein 95 (PSD-95), which binds the PDZ-domain recognition motif at the carboxyl terminus of ERBB4; and several adapter proteins, including the SRC homology domain 2-containing transforming protein (SHC1), growth factor receptor-bound protein 2 (GRB2), growth factor receptor-bound protein 7 (GRB7), CT10 regulator of kinase (CRK), and the CRK-like protein (CRKL) ( Culouscou et al, 1995 ; Sepp-Lorenzino et al, 1996 ; Elenius et al, 1997b ; Fiddes et al, 1998 ; Olayioye et al, 1998 ; Pinkas-Kramarski et al, 1998b ; Wang et al, 1998 ; Elenius et al, 1999 ; Jones et al, 1999 ; Olayioye et al, 1999 ; Garcia et al, 2000 ; Huang et al, 2000 , 2002 ; Sweeney et al, 2000 ; Puricelli et al, 2002 ; Carpenter, 2003a ,b; Schulze et al, 2005 ; Chuu et al, 2008 ; Kaushansky et al, 2008 ; Ishibashi et al, 2013 ; Roskoski, 2014 ; Li et al, 2015 ; Wang, 2017 ; Segers et al, 2020 ). Section II.H , which is focused on signaling by the soluble ERBB4 cytoplasmic domain (4ICD), further discusses ERBB4 signaling effectors, some of which are not mentioned in Section II.D .…”
Section: Structure and Function Of Erbb4mentioning
confidence: 99%
See 1 more Smart Citation
“…4 ). Altogether, an incomplete list of the proteins that apparently mediate ERBB4 function via physical and functional interactions with the ERBB4 cytoplasmic domain includes the Rous sarcoma virus protein tyrosine kinase (SRC); the Abelson-related protein tyrosine kinase (ABL2); the spleen-associated protein tyrosine kinase (SYK); the Janus kinase 1 (JAK1); protein tyrosine phosphatase non-receptor type 11 (PTPN11); phospholipase C gamma-2 (PLCG2); phosphatidylinositol 4,5-bisphosphate 3-kinase catalytic subunit alpha isoform (PIK3CA) via its p85 regulatory subunit; the Casitas B-lineage lymphoma ubiquitin ligase (CBL); the second guanine nucleotide exchange factor named after the sixth letter of the Greek alphabet (VAV2); the rat sarcoma virus protein (RAS) GTPase activating protein RASA1; the signal transducer and activator transcription factors STAT1 and STAT5a; the Yes-associated protein 1 (YAP1); the tumor suppressor oxidoreductase WWOX; postsynpatic density protein 95 (PSD-95), which binds the PDZ-domain recognition motif at the carboxyl terminus of ERBB4; and several adapter proteins, including the SRC homology domain 2-containing transforming protein (SHC1), growth factor receptor-bound protein 2 (GRB2), growth factor receptor-bound protein 7 (GRB7), CT10 regulator of kinase (CRK), and the CRK-like protein (CRKL) ( Culouscou et al, 1995 ; Sepp-Lorenzino et al, 1996 ; Elenius et al, 1997b ; Fiddes et al, 1998 ; Olayioye et al, 1998 ; Pinkas-Kramarski et al, 1998b ; Wang et al, 1998 ; Elenius et al, 1999 ; Jones et al, 1999 ; Olayioye et al, 1999 ; Garcia et al, 2000 ; Huang et al, 2000 , 2002 ; Sweeney et al, 2000 ; Puricelli et al, 2002 ; Carpenter, 2003a ,b; Schulze et al, 2005 ; Chuu et al, 2008 ; Kaushansky et al, 2008 ; Ishibashi et al, 2013 ; Roskoski, 2014 ; Li et al, 2015 ; Wang, 2017 ; Segers et al, 2020 ). Section II.H , which is focused on signaling by the soluble ERBB4 cytoplasmic domain (4ICD), further discusses ERBB4 signaling effectors, some of which are not mentioned in Section II.D .…”
Section: Structure and Function Of Erbb4mentioning
confidence: 99%
“…Thus, it is not surprising that WWOX is also a tumor suppressor. WWOX appears to function in part by binding nuclear oncoproteins, including several transcription factors, and sequestering them in the cytoplasm ( Aqeilan et al, 2005 ; Citri and Yarden, 2006 ; Blobel et al, 2009 ; Li et al, 2015 ; Pospiech et al, 2018 ); however, the tumor suppressor activity of WWOX may also be dependent on its 17b-hydroxysteroid dehydrogenase activity ( Gluz et al, 2009 ; Krishnamurthy et al, 2012 ; Li et al, 2015 ; Pospiech et al, 2018 ). It has been reported that WWOX constitutively localizes the 4ICD to the cytoplasm ( Aqeilan et al, 2007 ; Segers et al, 2020 ).…”
Section: Structure and Function Of Erbb4mentioning
confidence: 99%
“…tory effect of lead on GPDH induction is consistent with the in vivo observations of hypomyelination. 232 In addition, the C6 glioma cell line has also been used in experimental research to evaluate the neurotoxicity of other compounds, including tri-ortho-cresyl phosphate, 233 manganese 234 or methylmercury. 235 Therefore, this cell line constitutes another alternative model available for neurotoxicity research in vitro.…”
Section: C6 Cells: a Rat Glioma Cell Linementioning
confidence: 99%
“…The significance of WWOX laid the foundations for thorough investigations of its role not only in tumor suppression but also in regulating metabolism, cellular homeostasis, and DNA damage response [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. WWOX gene expression was found to be downregulated or lost in several types of cancer [ 15 ] and this was related to the poor prognosis in tumors of the breast [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], liver [ 24 , 25 , 26 ], ovary [ 27 , 28 ], bladder [ 29 , 30 ], and kidney [ 31 ], as well as to glioblastoma [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%